These truths we hold : Judasim in an age of truthiness - Zierler, Wendy; Garroway, Joshua D. (Hebrew Union College Press, 2022)
"The authors of this collection, comprising leading scholars, journalists, entertainers, and religious leaders, were asked to examine the idea of truth from a variety of Jewish textual and disciplinary perspectives-biblical, rabbinic, liturgical, scientific, and artistic. The volume's intention is to hold out the hope that deep, thoughtful teaching from some of the world's leading Jewish voices might lead not to deeper understanding not just of Jewish texts, but of the nature and accessibility of truth itself"--